The equation to be solved is (2x+48)^1/2 - x = 0

(2x+48)^1/2 - x = 0

=> (2x+48)^1/2 = x

square both the sides

2x + 48 = x^2

=> x^2 - 2x - 48 = 0

=> x^2 - 8x + 6x - 48 = 0

=> x(x -...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The equation to be solved is (2x+48)^1/2 - x = 0

(2x+48)^1/2 - x = 0

=> (2x+48)^1/2 = x

square both the sides

2x + 48 = x^2

=> x^2 - 2x - 48 = 0

=> x^2 - 8x + 6x - 48 = 0

=> x(x - 8) + 6(x - 8) = 0

=> (x + 6)(x - 8) = 0

**The solution of the equation are x = -6 and x = 8**

We have to solve for x given that (2x+48)^1/2 - x = 0

(2x+48)^1/2 - x = 0

=> (2x+48)^1/2 = x

square both the sides

=> (2x + 48 ) = x^2

=> x^2 - 2x - 48 = 0

=> x^2 - 8x + 6x - 48 = 0

=> x(x - 8) +6(x - 8) = 0

=> (x - 8)(x + 6) = 0

From x - 8 = 0, we get x = 8

and from x + 6 = 0, we get x = -6

**Therefore x can take the values -6 and 8**.